Weakly Quasi (τ1, τ2)-Continuous Functions - Chiangpradit, Monchaya; Sompong, Supannee; Boonpok, Chawalit (International journal of analysis and applications, 2024)
This paper deals with the notion of weakly quasi (τ1, τ2)-continuous functions. Furthermore, some characterizations of weakly quasi (τ1, τ2)-continuous functions are discussed.